Engineering Geology and Slope Stability of West Pit Coal Mine of PT. Tawabu Mineral Resource, East Kalimantan, Indonesia - Rama Tri Saksono; I Gde Budi Indrawan; Wahyu Wilopo (Geological Engineering Department Universitas Gadjah Mada, 2022)
The research area was located in the west pit of the open pit coal mine of PT. Tawabu Mineral Resource (TMR) which is located in Bengalon District, East Kutai Regency, East Kalimantan Province, Indonesia. The research was driven by several landslides that occurred in the research area, but the engineering geological conditions and stability of the remaining slopes have not been evaluated. The objectives of this study were to better understand the engineering geological conditions and stability of the research area. The engineering geological conditions (i.e., geomorphology, rock and soil, geological structure, and groundwater conditions) were evaluated by photogrametric analyses, field observations, and analyses of borehole logs and laboratory test results. The slope stability analyses were firstly carried out by conducting back stability analyses of failed slope on the northern lowwall slope segment. The shear strength parameters obtained from the back analyses were then used for forward stability analyses of the remaining 10 lowwall and highwall slopes. The slope stability analyses involved deterministic and probabilistic analyses, under static and dynamic using the limit equilibrium method (LEM). The results showed that the research area and the surrounding consisted of two geomorphological units, namely the alluvial plain and structural hills. Rocks in the study area consisted of claystone, sandstone, and coal with a general layer strike direction of N59°E – N63°E with a dip of 19°-26°. These rocks were grouped into two lithological units, namely the alternating of claystone and sandstone unit and alternating of sandstone and claystone unit. The geological structures were identified on the highwall, from west to east namely major sinistral shear fault with a relative direction of NNE-SSW, two minor sinistral shear faults with a relative direction of NE-SW, and a major dextral shear fault with a relative direction of NW-SE. These geological structures were interpreted as being formed by the folding process. The groundwater level was estimated at a level of -45 m to 20 m. The slope stability analyses showed that only the East HW-4 slope, which was located on the east highwall, was unstable. It is recommended to optimize the slope by either lowering the groundwater elevation by 4 m from the actual level or by reducing the angle the overall slope to 31°.